Answer:
Explanation:
To find the inverse of the function you need to swap x and y
g(x)=y so therefore if you switch x and y, you get
x= 2y+ 10/4
Next, you need to get all of the values on the y side over to the x side. To do this you need to subtract 10/4 from the y side of the equation.
x-10/4=2y+10/4-10/4
The end product of this should be... (This is not your answer)
x-10/4=2y
Now you need to get rid of the 2 on the y side. To do this you need to divide both sides of the equation by 2
2/x-10/4=2y/2
So your answer is...
x-10/4 over 2 = y
OR
2/x + 5/4 = y
Lots of love,
-Kiddoo <3